2002
DOI: 10.1037/0096-1523.28.2.396
|View full text |Cite
|
Sign up to set email alerts
|

Ideomotor compatibility in the psychological refractory period effect: 29 years of oversimplification.

Abstract: Four experiments examined whether the psychological refractory period (PRP) effect can be eliminated with ideomotor compatible (IM) but not stimulus-response compatible (SR) tasks, as reported by A. G. Greenwald and H. G. Shulman (1973). Their tasks were used: a left or right movement to a left-or right-pointing arrow (IM) or to the word left or right (SR) for Task 1; saying "A" or "B" (IM) or "1" or "2" (SR) to an auditory A or B for Task 2. The stimulus onset asynchronies were 0, 100, 200, 300, 500, and 1,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(104 citation statements)
references
References 34 publications
9
94
1
Order By: Relevance
“…Greenwald (1972;Greenwald & Shulman, 1973) tested this ideomotor approach to dual-task interference by comparing dual-task performance for two ideomotor compatible tasks with that for other task combinations of one or two non-ideomotor compatible tasks. Consistent with ideomotor theory, the dual-task interference effect was largely reduced with two ideomotor compatible tasks (see also Greenwald, in press;Lien, Proctor, & Allen, 2002, for further discussion).…”
supporting
confidence: 52%
“…Greenwald (1972;Greenwald & Shulman, 1973) tested this ideomotor approach to dual-task interference by comparing dual-task performance for two ideomotor compatible tasks with that for other task combinations of one or two non-ideomotor compatible tasks. Consistent with ideomotor theory, the dual-task interference effect was largely reduced with two ideomotor compatible tasks (see also Greenwald, in press;Lien, Proctor, & Allen, 2002, for further discussion).…”
supporting
confidence: 52%
“…G&S's result was recently called into question by a nonreplication (Lien, Proctor, & Allen, 2002;LP&A). Experiment 1 replicated G&S's perfect timesharing finding when instructions for the ISI ϭ 0 dual task emphasized giving simultaneous and rapid responses to simultaneous stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Mean latencies of correct responses for single-task and dualtask conditions of Experiment 1, shown for the visual-manual task (A and B), the auditory-vocal task (C and D), and the average of both tasks (E and F). In Condition LPA (n ϭ 17), instructions based on those used by Lien, Proctor, and Allen (2002) emphasized that stimuli for the interstimulus interval (ISI) ϭ 0 dual-task condition were simultaneous. In Condition GS (n ϭ 16), instructions based on those used by Greenwald and Shulman (1973) urged rapid responding for all tasks and simultaneous responding in the ISI ϭ 0 condition.…”
Section: Methodsmentioning
confidence: 99%
“…Both of Greenwald and Shulman's (1973) experiments showed a PRP effect when one task was ideomotor compatible and the other was S -R compatible, as did all of Lien, Proctor, and Allen's (2002) experiments, which closely replicated the methods of Greenwald and Shulman's study (see also Kantowitz &Knight, 1976, andKlapp, Porter-Graham, &Hoifjeld, 1991, for similar results with continuous tapping and shadowing tasks). Across the experiments reported by Greenwald and Shulman and by Lien, Proctor, and Allen (2002), the PRP effect tended to be larger when T2 was ideomotor compatible than when T1 was, suggesting that although serial response selection is still required for an ideomotor compatible task, it is faster than for a nonideomotor compatible task.…”
Section: Compatibility In Dual-task Performance Can Prp Effects Be Elmentioning
confidence: 97%
“…Most subsequent citations of their study have also stated that the results demonstrated that the PRP effect was eliminated with two ideomotorcompatible tasks (e.g., De Jong, 1995;Meyer & Kieras, 1997a;Pashler, 2000). Lien, Proctor, and Allen (2002) questioned the generalization that the PRP effect is eliminated with two ideomotor compatible tasks because of the discrepancy in results between Greenwald and Shulman's Experiments 1 and 2. We noted that the reason for the discrepant results is not obvious because the designs of those two experiments differed in several potentially crucial respects (the aforementioned differences in instructions and SOAs, as well as the inclusion of single-task blocks in Experiment 2 but not in Experiment 1).…”
Section: Compatibility In Dual-task Performance Can Prp Effects Be Elmentioning
confidence: 99%